Exploring luxury brand country of origin impact on purchasing behaviors in India: A conceptual framework. Issue 3 (7th September 2015) - Schultz, Don; Jain, Varsha
Abstract : Purpose: – Luxury brands' marketing efforts have traditionally focussed on developed nations since that has comprised the majority of consumer demand. However, double-digit growth in developing nations such as India and China, have attracted the attention of most luxury brand managers. Using cue utilization theory, the authors conducted a qualitative study in two phases comprised of first, focus group discussions (FGD), structured observations (SO) and second, In-Depth Interviews (IDI) to understand the effects of country of origin (COO) on Indian consumers' current day purchasing behaviors with luxury products. The paper aims to discuss these issues. Design/methodology/approach: – Using cue utilization theory, the authors conducted a qualitative study in two phases comprised of first, FGD, SO and second, IDI to understand the effects of COO on Indian consumers' current day purchasing behaviors with luxury products. A conceptual framework has been developed that should help luxury brands formulate marketing strategies for this booming market. Findings: – Further, this study found that COO affects the exploration of luxury brands and this process is carried out digitally and primarily with friends. Luxury brand managers can insert detailed information about COO on web sites and can understand the keywords used in the search engines to facilitate consumers using appropriate consideration data. This research also found that COO is compared on the basis of quality, features and innovation. Research limitations/implications: – The results of this study are only from one emerging country, i.e., India. Similar studies should be carried out in other emerging nations. Additionally, developed countries can also carry out comprehensive research in this domain as their behavior is also changing for COO and luxury brands. Originality/value: – This insight can be used by the brand managers and they can develop apps and web sites that would help the consumers to compare the COO for their products. Additionally, this research found that COO helps the luxury consumers to evaluate the brands and how they associate it with consumer images. Luxury brand managers need to be conscious when their countries products/ brands have been rated low by the consumers as it could result in consumers simply discarding them from their consideration set.